The 1st i-EUS consensus on the management of pancreatic fluid collections – Part 2 - Capurso, Gabriele; Coluccio, Chiara; Rizzo, Giacomo Emanuele Maria; Crinò, Stefano Francesco; Cucchetti, Alessandro; Facciorusso, Antonio; Hassan, Cesare; Amato, Arnaldo; Auriemma, Francesco; Bertani, Helga; Binda, Cecilia; Cipolletta, Fabio; et al. (Digestive and liver disease, 2024)
Pancreatic fluid collections (PFCs), including pancreatic pseudocysts (PPs) and walled-off pancreatic necrosis (WON), are common complications of pancreatitis and pancreatic surgery. Historically, the treatment of these conditions has relied on surgical and radiological approaches. The treatment of patients with PFCs has already focused toward an endoscopy-based approach, and with the development of dedicated lumen-apposing metal stents (LAMS), it has almost totally shifted towards interventional Endoscopic Ultrasound (EUS)-guided procedures. However, there is still limited consensus on several aspects of PFCs treatment within the multidisciplinary management. The interventional endoscopy and ultrasound (i-EUS) group is an Italian network of clinicians and scientists with special interest in biliopancreatic interventional endoscopy, especially interventional EUS. This manuscript focuses on the second part of the results of a consensus conference organized by i-EUS, with the aim of providing evidence-based guidance on several intra- and post-procedural aspects of PFCs drainage, such as clinical management and follow-up.